Respuesta :

Answer:

D. (f - g)(x) = 4x^3 + 7x^2 - 6x + 1

Step-by-step explanation:

You need to subtract g(x) from f(x).

(f - g)(x) = f(x) - g(x) =

= 4x^3 + 7x^2 - 2x - 1 - (4x - 2)

Distribute the negative sign at the left of the parentheses as you would distribute a -1. Every sign inside the parentheses changes.

= 4x^3 + 7x^2 - 2x - 1 - 4x + 2

Combine like terms.

= 4x^3 + 7x^2 - 6x + 1

Answer: D. (f - g)(x) = 4x^3 + 7x^2 - 6x + 1

Answer:

4x^3+7x^2-6x+1

Step-by-step explanation:

f(x) = 4x^3 +7x^2 -2x-1

g(x) = 4x-2

f(x) - g(x) = 4x^3 +7x^2 -2x-1 - ( 4x-2)

Distribute the minus sign

                4x^3 +7x^2 -2x-1 - 4x+2

Combine like terms

                   4x^3+7x^2-6x+1

             

ACCESS MORE